Increased ratio of mature BDNF to precursor-BDNF in patients with major depressive disorder with severe anhedonia. (July 2020) - Wu, Congchong; Lu, Jing; Lu, Shaojia; Huang, Manli; Xu, Yi
Abstract: Background: Although studies have shown that severe anhedonia in patients with major depressive disorder (MDD) is associated with poor treatment outcomes, the biological mechanism of this feature is unclear. The aim of this study was to investigate the dysfunction of brain-derived neurotrophic factor (BDNF) metabolism, measured by the ratio of mature BDNF to precursor-BDNF, in MDD patients with severe anhedonia. Methods: We measured plasma levels of mature BDNF (mBDNF), precursor-BDNF (proBDNF), tissue plasminogen activator (tPA) and tropomyosin-related kinase B (trkB) in outpatients with MDD with anhedonia (n = 26), outpatients with MDD without anhedonia (n = 29) and age- and sex-matched healthy controls (HCs, n = 38) by enzyme-linked immunosorbent assay kits, and we calculated the ratio of mBDNF to proBDNF (M/P). We compared these biological determinants among the three groups and explored the interrelationships between anhedonia severity and BDNF metabolism. Results: The levels of mBDNF, proBDNF, and tPA and the ratio of M/P were identified with highly significant differences among the three groups. Compared with MDD patients without anhedonia and healthy controls, MDD patients with anhedonia showed higher level of the ratio of M/P, and it was positively associated with the SHAPS scores in MDD patients. Compared to healthy controls, the plasma tPA concentrations were higher in MDD patients with anhedonia but were not different from those in MDD patients without anhedonia. Conclusion: These results provide novel evidence regarding the relationship between anhedonia and plasma BDNF metabolism. The hypermetabolism of BDNF may be a function of anhedonia rather than other characteristics in MDD.